A comparative analysis of femoral nerve block with adductor canal block following total knee arthroplasty: A systematic literature review - Yugal Karkhur; Ramneek Mahajan; Abhimanyu Kakralia; Amol Prabhakar Pandey; Mukul Chandra Kapoor (Wolters Kluwer Medknow Publications, 2018)
Background: Patients undergoing total knee arthroplasty suffer from moderate-to-severe postoperative pain resulting in immobility-related complications and prolonged hospitalization. Femoral nerve block is associated with reduction in the quadriceps strength and increasing incidence of falls. Adductor canal block has been shown to be as effective as femoral nerve block without causing quadriceps weakness. Objectives: To compare outcomes of studies comparing adductor canal block and femoral nerve block in patients undergoing primary total knee arthroplasty. Data Sources: Original articles, published between July 2013 and April 2017, comparing the above interventions. Study Eligibility Criteria, Participants, and Interventions: Comparison of outcome measures of all original articles shortlisted by the PUBMED and Google Scholar databases search using key words, "adductor canal block; femoral nerve block; total knee arthroplasty; total knee replacement." Study Appraisal and Synthesis Methods: The primary outcome measures reviewed were: pain scores; interventional failure; post-operative opioid consumption; patient fall or near fall during postoperative rehabilitation; and length of stay. Results: The opioid consumption was found to be comparable with both the interventions on the first and second postoperative day. Patients administered adductor canal block had better quadriceps power, longer ambulation distance, and shorter length of hospital stay. Limitations: Of the studies reviewed five were retrospective and thus data quality amongst the studies may have been compromised. Conclusions and Implications of Key Findings: Mobilization and ambulation, which are both important for recovery after total knee arthroplasty are both inhibited less by adductor canal block.